Dobrostan psychiczny a efektywność pracy kuratora sądowego - Filipowski, Piotr (Pedagogika Społeczna Nova, 2026)
The article will touch upon the topic of probation officer effectiveness and present the factors influencing its level, it also takes a closer look at the issue of mental well-being and its impact on professional work. The article presents the results of a study on the impact of mental well-being on the effectiveness of probation officers. The research was carried out on the basis of a diagnostic survey method. The leading technique was a questionnaire. The Mental Well-being Questionnaire was used for the study, as well as a created scale for the study of effectiveness dimensions (economic, relational, organisational, declared). The research presented here found no correlation between economic, relational or organisational efficacy and psychological well-being. However, when analysing the data on declared effectiveness and the level of psychological well-being, it was found that high psychological well-being increases declared effectiveness among probation officers. The referenced research showed the need to implement a policy of concern for the mental well-being of those involved in educational and rehabilitation tasks, particularly among probation officers.